Utilização de agregados reciclados de alvenaria na produção de concreto para contrapisos - Tonus, Cristian Allan (2013)
With the prospects of reducing environmental impacts that currently are one of the most discussed themes in Brazilian society, specially in the field of civil construction, new technologies arised as a way to search for benefits to reduce the engendering of construction and demolition waste (RCD – acronim in Portuguese), as studied during this work, that aimed to show results of the utilization of red ceramic waste in the composition of concrete to subfloor. This work is going to verify the technical and economical viability of the use of RCD in concrete to subfloor comparing the final costs of those with the standard concrete. The method of work was divided in three stages, in the first stage, the granulometry of the samples was determined and assays of specific mass and water absorption were performed, a trace for the concrete was defined as 65,33% of coarse aggregate (RCD) and 34,67% of slender aggregate (sand). In the second stage rebating assays of frustcone were performed – Slump test, to recognize the consistency of the concrete by adding RCD and the exudation was tested to show the amount of exuding water that this concrete presented. Lastly, in the third stage, the test of resistance to simple compression of the cylindrical samples of concrete was performed, during the 7, 14 and 28 days to notice the mechanical behavior of this new concrete. The studied samples presented large differences on resistance, the concrete with RCD showed high resistance and could be used for another ai mor function, or even be used as subfloor with large capacity of charge and a high performance. About the costs, the RCD concrete presented a lower value (in R$/m³) compared to standard concrete due to the substitution of crushed stones for red ceramic waste.